Strategic recruitment and selection in Malaysian small and medium enterprises: unravelling the evidence of fit - Abraham, Mathew (2020)
Organisations that demonstrate effective human resource management (HRM) practices experience higher productivity from employees. The antecedent is to establish and implement human resource functions or processes that bring out the best in employees. Generally, larger organisations have more sophisticated and wellstructured HRM practices. The perception is HRM practices in large organisations are easy to replicate in small and medium enterprises (SMEs). Certainly, SMEs face many challenges unique to their business environment hence the solutions are specific to these challenges. Therefore, issues affecting people, in this instance HRM issues would require highly specific human resource process interventions to suit the SMEs needs. A very vital and highly specific element is the strategic recruitment and selection process in SMEs. Hence, this study focuses on the importance of strategic recruitment and selection practices in Malaysian SMEs and the significance of fit specifically person-job (PJ) and person-organisation (PO) fit. Literature indicates there is a lack of sufficient studies that look at the effect and application of PO and PJ fit dimension in the recruitment and selection function specifically in Malaysian SMEs.